Phylogeny and an integrated biogeography of Acanthotetilla Burton, 1959 (Demospongiae: Spirophorida: Tetillidae): two-way traffic on the peri-African track - Fernandez, Julio C. C.; Peixinho, Solange; Hajdu, Eduardo (Zootaxa, 2012)
The recent description of Indonesian and Brazilian species of Acanthotetilla motivated the onset of a phylogenic andbiogeographic revision of this taxon, to figure whether it had an Atlantic or an Indo-Pacific origin, and whether a Tethyanor southern African route might have been followed. A datamatrix with 27 morphological characters and 63 characterstates was tabulated and run on PAUP*4.0 using a parsimony algorithm. The resulting phylogenetic hypothesis wasconverted in a Taxon Area Cladogram (TAC) and used as a basis for a comparative analysis of the evolutionary history ofthe comprised biogeographic provinces, which in turn was contrasted to additional poriferan phylogenies. TheAcanthotetilla TAC was further used in a dispersal-vicariance analysis with the software DIVA 1.1, and in a manualpanbiogeographic analysis. The resulting preferred tree has a high Bootstrap support, as a consequence of the largest everratio of morphological character states employed per OTU among published poriferan phylogenies. The result showsCentral Indo-Pacific provinces basal to the whole clade, then Western Indo-Pacific provinces basal to the Tropical WesternAtlantic ones, thus unequivocally suggesting colonization of the latter from the former, and likely following a southernAfrican route. It is suggested here that this might have been accomplished through rafting on rings of the Agulhas Current.The dispersal – vicariance analysis undertaken postulated a recent dispersal event with recolonization of the Seychellesfrom the western Atlantic. The panbiogeographic map for Acanthotetilla also points to Western Indo-Pacific origin ofTropical Western Atlantic species. A comparison with 10 additional sponge phylogenies did not recover any prevailingtrends for the relationships of the major areas utilized in the present analyses, but identified two taxa with likely CentralIndo-Pacific origins (Thrinacophora, Placospongia), and one with a Western Indo-Pacific origin of Tropical WesternAtlantic clades (Petromica). The integrated biogeographic approach to the analysis of Acanthotetilla data permitted distinct interpretations, which might have been overlooked in case a single method was chosen a priori.